A bis(silylene)pyridine pincer ligand can stabilize mononuclear manganese(0) complexes: facile access to isolable analogues of the elusive d7-Mn(CO)5 radical. Issue 29 (11th July 2022) - Kalra, Shweta; Pividori, Daniel; Fehn, Dominik; Dai, Chenshu; Dong, Shicheng; Yao, Shenglai; Zhu, Jun; Meyer, Karsten; Driess, Matthias
Abstract : An isolable bis(silylene)pyridine stabilized manganese(0) complex {κ 3 -[SiNSi]Mn(dmpe)}, isolobal to elusive Mn(CO)5 radical has been synthesized and fully characterised. Abstract : Using the potentially tridentate N, N′ -bis( N -heterocyclic silylene)pyridine [SiNSi] pincer-type ligand, 2, 6- N, N′ -diethyl-bis[ N, N′ -di- tert -butyl(phenylamidinato)silylene] diaminopyridine, led to the first isolable bis(silylene)pyridine-stabilized manganese(0) complex, {κ 3 -[SiNSi]Mn(dmpe)} 4 (dmpe = (Me2 P)2 C2 H4 ), which represents an isolobal 17 VE analogue of the elusive Mn(CO)5 radical. The compound is accessible through the reductive dehalogenation of the corresponding dihalido (SiNSi)Mn(ii ) complexes 1 (Cl) and 2 (Br) with potassium graphite. Exposing 4 towards the stronger π-acceptor ligands CO and 2, 6-dimethylphenyl isocyanide afforded the related Mn(0) complexes κ 2 -[SiNSi]Mn(CO)3 (5 ) and κ 3 -[SiNSi]Mn(CNXylyl)2 (κ 1 -dmpe) (6 ), respectively. Remarkably, the stabilization of Mn(0) in the coordination sphere of the [SiNSi] ligand favors the d 7 low-spin electronic configuration, as suggested by EPR spectroscopy, SQUID measurements and DFT calculations. The suitability of 4 acting as a superior pre-catalyst in regioselective hydroboration of quinolines has also been demonstrated.